Expanding understanding of elite athlete parenthood in socio-cultural context: a meta-synthesis of qualitative media research findings on motherhood and sport - Kulkarni, S.; McGannon, K. R.; Pegoraro, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2023)
As athlete mothers continue with sport careers and gain visibility in the media, scholars have explored media representations of high profile athlete mothers in discourses, from several disciplinary perspectives. This paper focuses on synthesizing these multi-disciplinary qualitative media research findings, to gain understanding of key themes that form complex socio-cultural meanings of motherhood and elite sport. Fifteen qualitative media studies were selected for inclusion in this meta-synthesis after searching eight electronic databases. Our descriptive synthesis of multi-disciplinary literature is presented through three themes: (a) (in)compatibility between athlete and mother identities, (b) motherhood as an individual responsibility, and (c) controlling the body. These findings were further synthesized into two new narrative themes: (a) entitlement to impose and (b) maternal activism and new ethic of care. Future research recommendations include expanding descriptive themes and new narratives through investigating additional mainstream and digital media forms, sport contexts, and intersectional identities.